Modeling a Controlled-Floating Space Robot for In-Space Services: A Beginner’s Tutorial - Seddaoui, Asma; Saaj, Chakravarthini Mini; Nair, Manu Harikrishnan (Frontiers in Robotics and AI, 2021)
Ground-based applications of Robotics and Autonomous Systems (RAS) are fast advancing, and there is a growing appetite for developing cost-effective RAS solutions for in-situ servicing, debris removal, manufacturing and assembly missions. An orbital space robot, i.e. a spacecraft mounted with one or more robotic manipulators, is an inevitable system for a range of future in-orbit services. However, various practical challenges make controlling a space robot extremely difficult compared to its terrestrial counterpart. The state-of-the-art of modelling the kinematics and dynamics of a space robot, operating in the free-flying and free-floating modes, has been well studied by researchers. However, these two modes of operation have various shortcomings, which can be overcome by operating the space robot in the controlled-floating mode. This tutorial paper aims to address the knowledge gap in modelling complex space robots operating in the controlled-floating mode and under perturbed conditions. The novel research contribution of this paper is the refined dynamical model of a chaser space robot, derived with respect to the moving target whilst accounting for the internal perturbations due to constantly changing Centre ofMass, the inertial matrix, Coriolis and Centrifugal terms of the coupled system; it also accounts for the external environmental disturbances. The nonlinear model presented accurately represents the multi-body coupled dynamics of a space robot, which is pivotal for precise pose control. Simulation results presented demonstrate the accuracy of the model for closed-loop control. In addition to the theoretical contributions in mathematical modelling, this paper also offers a commercially viable solution for a wide range of in-orbit missions.